The first human retroviruses: the human T lymphotropic viruses (HTLVs) - Hall, William (Henry Stewart Talks, 2007)
Human retroviruses, HTLV-1, HTLV-2, Epidemiology of infection, Clinical features of infection, Adult T-cell leukemia/lymphoma (ATLL), Molecular pathogenesis of ATLL, Transgenic mouse model of ATLL
Archived at 2018/05/31